Experiências de casas-museu em Portugal e Brasil: vidas, lugares e memórias - Gameleira, Raissa de Albuquerque (2022)
The research is focused on the theory and practice of design regarding historic house museums. It is based upon architectural studies on both museums and housing, tied to concepts regarding poetics of space, morphology, perception, as well as the relationship between practical life and imaginative memory. As a museum, the studied typology needs to imprint, within the exhibition environment, practices that lead it to be an institution of preservation and learning. In this sense, the main challenge perceived in house-museums is to transform a residential building, with its objects and memories, into a museological institution responsible for preserving, educating, communicating, and other intrinsic actions. The research question emerges from the gap perceived in historic house museums research: how do architecture and museography influence the perception of a historic house museum as imaginative memory? In this research, the relationships between form, image, exhibition spaces and housing spaces, as well as the public interaction with such aspects, cause reflective considerations about housing architecture and museography design. Thus, space can be considered a form of language, essential to the understanding of the intimate life there portrayed. The initial hypothesis is then to identify the architectural elements that, alongside museography, enable the communication of a given imaginative memory for a house-museum. The research has been developed with mixed methodological procedures, with tools and instruments of analysis and interpretation that allowed a broad understanding of the phenomena, their sense and meaning, through a process of interactive and simultaneous steps. To this extent, we have selected four historic house museums as case studies (Fundação Amália Rodrigues Casa-Museu, Fundação Medeiros e Almeida Casa-Museu, Fundação Ema Klabin Casa Museu e Casa Guilherme de Almeida), researched within a framework that encompasses: Context (life and place), Space and form (visual and morphological analysis), Use and Perception (interviews with working staff and visitors). The data gathered were cross analysed, allowing the development of parameters confronted with the revised state of the art. The conclusions rediscuss the problem initially stated, suggesting ways to rethink housing poetics and imaginative memory within the process that changes a house into a historic house museum.